PERANAN TUANKU NAN BARAMPEK MEREVITALISASI MAJID SEBAGAI PUSAT PEMBINAAN MASYARAKAT NAGARI MADANI - Edi Rosman; Elfiani Elfiani; Pendi Hasibuan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Tuanku Nan Barampek is a local institution that comes from local wisdom. Its existence in the context of the Minangkabau Society has been historical from the past to the present. Existence still survives to this day. The dynamics of the Minangkabau community which has undergone social and cultural transformation have not caused this institution to lose its local symbol and identity. The presence of this research is to get an idea of how the actual existence of Tuanku nan Barampek is in the current social configuration of Minangkabau society. One of the initial arguments that this institution still exists is because in Minangkabau there are nagari and jorong which have facilities for the life of Tuanku nan Barampek itself. The life and work of Tuanku nan barampek is the mosque in Jorong and Nagari. Furthermore, what is the role of Tuanku Nan Barampek himself in prospering the mosque, how is the effort he makes in making the mosque a center for community development. Ideally, Tuanku Nan Barampek should be the government's partner in building civil society because one of the parameters of civil society in the context of civil society is realizing Islamic values in people's lives, implementing ABS-SBK customary values and so on. Research shows that Tuanku Nan Barampek still exists, but plays less of a role in revitalizing the mosque. while the effort made is to accept the mandate in accordance with the times.Keywords: Tuanku Nan Barampek, Mosque, Civil Society.